Oranisational Responses to Compassion Fatigue and Burnout in Trauma Counsellors: A Multi-Organisational Investigation - Geldenhuys, Eone (My University, 2006)
A traumatic event is characterised by a situation that involves the actual or threatened death or injury to one’s self or others (Hesse, 2002). Figley (1999) described traumatic stress from another perspective in that individuals exposed to a traumatised person, may experience emotional upset and may become a victim, indirectly of the traumatic event. Secondary Traumatic Stress (STS) emerges suddenly and without warning. The sufferer of STS often experience feelings of confusion and helplessness. Compassion fatigue, an equivalent to STS first made appearance in studies of job burnout in the helping professions to describe a decline in compassionate feelings toward patients or clients in need. Compassion fatigue has since been widely used external to the occupational context, thus in the wider social community (Kinnick, Krugman & Cameron, 1996). In literature, a clear frame is presented by the Constructivist Self Development Theory and focuses on the multifaceted interaction between the ind ividual and the environment. According to this theory individuals construct their own realities. The self is the seat of the individual’s identity and inner life, which encompasses four interrelated aspects: selfesteem, ego resources, psychological needs and cognitive schemas. Traumatic experiences are encoded in the verbal and imagery systems of the memory. Adaptation to trauma reflects an interaction between life experiences and the self (McCann & Pearlman, 1990). Neurotic anxiety, Type A syndrome, locus of control, flexibility, and introversion as the five personality traits, guide an individual’s responses to stress (Cherniss, 1980). Not only personality traits, but also career goals and previous experiences may influence an individual’s suscep tibility to stress. In contrast, coping strategies are influenced by social support such as family involvement and friends, and the load of stress on the individual (Harel, B. Kahana and E. Kahana, 1993). Freud suggested that fixation on trauma is biolo gically based and posttraumatic stress disorder is associated with complex abnormalities in several biological systems (Van der Kolk and Saporta, 1993). When considering the complexity of our biological system combined with the complexity of the human psyche, trauma counselling is energy consuming on both the victim and the counsellor. An additional theory explored was the Psychoanalytical theory which focuses on the intrapsychic processes and infantile conflict (Brett, 1993). Three basic assumptions are the core of the psychoanalytic theory, according to Meyer, Moore and Viljoen (1997). These are: psychosocial conflict, biological and psychological determinants, and mechanistic assumption based on natural sciences and indicates that an individual functions like a mechanism with energy and the functions thereof. Considering the difference between compassion fatigue and burnout, numerous researchers indicate the importance of distinguishing between these concepts. Figley (1999), indicates burnout as a result of emotional exhaustion and specifies that it also has a gradual emergence, in contrast to compassion fatigue which emerge suddenly and is associated with feelings of hopelessness and confusion, although the recovery rate is faster than that of burnout. According to Maslach (1982), burnout is: a syndrome of emotional exhaustion, depersonalisation and reduced personal accomplishments. Burnout may also be a logic outcome of lower levels of autonomy, control over practice, collaborative working relationships, and organisational trust as indicated by Spence Laschinger, Shamian and Thomson (2001. According to Hesse (2002), organisations may introduce interventions to assist employees in combating symptoms of compassion fatigue and burnout, or the foreseeing event of these symptoms occurring. These are: reduction of the number of caseloads each trauma counsellor are responsible for and provision of supervision and group support programmes to assist employe es in rendering these effects. Furthermore, organisations should ensure adequate benefits, staff development opportunities, regular leave, informed consent as a standard organisational policy to inform new counsellors of the risks involved in trauma counselling and expressive staff meetings An unfavourable effect may be caused by suffering therapists to their organisations in that the quality and effectiveness of the organisation's work may be compromised. Therapists who do not address compassion fatigue and burnout are likely to experience more disruption of their empathic abilities, resulting in frequent incomplete therapies (Waldrop, 2003). The objective of this research is to determine the organisational responses towards compassion fatigue and burnout in trauma counsellors. A comparison between organisational responses across multiple organisations model will be made to explore the effects of the various responses. Furthermore, the study will investigate the influences of organisational responses on compassion fatigue and burnout considering the influences individual differences of the trauma counsellors may have. The need to establish the organisational responses towards compassion fatigue and burnout in any given organisation may assist researchers, employees and organisations alike to proactively intervene in such incidence. Not only is it ethical to intervene but potential problems concerning employees may also become legality. The Occupational Health and Safety Act is a legal guide provided for employees and employers alike. Concerning the research design, a quantitative approach was employed to reach the research objectives. The target population for this study included counsellors working with trauma survivors. No volunteer counsellors were used for the reason that different responses are associated with volunteer counsellors beyond the scope of this study. The sample comprised of 25 (n) trauma counsellors in total. The total sample of 25 counsellors participating in the study, 19 were female and five (5)were male, with one response missing. The method of data collection was by means of structured questionnaires, more specifically, compassion fatigue and burnout was measured through the Professional Quality of Life: Compassion Satisfaction and Fatigue Subscales – Revision III (ProQol – RIII) and the Organisational questionnaire which was constructed by the researcher. The reliability scores of the ProQol – RIII obtained by the researcher indicated the first subscale, compassion satisfaction .92, the burnout subscale with an alpha of .62 and lastly compassion fatigue subscale with an alpha of .66. All statistical analysis was obtained with the assistance of the SAS Programme (SAS Institute, 2000). Descriptive statistics were used to analyse the data of the different organisations (Kerlinger & Lee, 2000). Content analysis was used to describe each organisation and organisational responses to compassion fatigue and burnout. Profiles for each organisation were developed ant in that the relationship between organisational responses and possible compassion fatigue was examined. The most prominent results were the following: Unanimous responses to no provision of primary interventions such as change of line of authority (70%), restructuring of organisational units in order to prevent monotony (76%), establishment of reward systems (81%), and information regarding issues concerning the Occupational Health and Safety Act (81%). Agreement among respondents that organisations do not providing time management training (86%), conflict management training (86%), focus groups or support groups (80), and health promotional activities such as weight-watchers (75%) were reached. Unanimous agreement was also observed regarding organisations not providing in-house counselling or referrals were. All organisations have average to low compassion satisfaction scores and all organisations tend to have average to high compassion fatigue with burnout being lower for all organisations except Organisation 1 with a tendency of higher burnout. Due to not finding phenomenal significant relationship between the organisation profiles when addressing the predictive power of organisational responses, the predictive power when individual differences are accounted for, became irrelevant. Janik (1995), stipulates that employees in every domain are at risk of developing compassion fatigue. These include correctional officers, counsellors, psychologists, social workers, emergency response personnel, and medical staff. We as employees and employers must unite to assist each other in combating these phenomena.
Master of Arts - Psychology
Keywords: Counsellors; fatigue; Burnout; compassion